Cell-Based Therapy Manufacturing in Stirred Suspension Bioreactor: Thoughts for cGMP Compliance - Nath, Suman C.; Harper, Lane; Rancourt, Derrick E. (Frontiers in Bioengineering and Biotechnology, 2020)
Cell-based therapy (CBT) is attracting much attention to treat incurable diseases. In recent years, several clinical trials have been conducted using human pluripotent stem cells (hPSCs), and other therapeutically potential cells. Various private- and government-funded organizations are investing in finding permanent cures for diseases that are difficult or expensive to treat over a lifespan, such as age-related macular degeneration, Parkinson's disease, or diabetes, etc. Clinical-grade cell manufacturing requiring current good manufacturing practices (cGMP) has therefore become an important issue to make safe and effective CBT products. Current cell production practices are adopted from conventional antibody or protein production in the pharmaceutical industry, wherein cells are used as a vector to produce the desired products. However, with CBT the “cells are the final products” and sensitive to physico- chemical parameters and storage conditions anywhere between isolation and patient administration. In addition, the manufacturing of cellular products involves multi- stage processing, including cell isolation, genetic modification, PSC derivation, expansion, differentiation, purification, characterization, cryopreservation, etc. Posing a high risk of product contamination, these can be time- and cost- prohibitive due to maintenance of cGMP. The growing demand of CBT needs integrated manufacturing systems that can provide a more simple and cost-effective platform. Here, we discuss the current methods and limitations of CBT, based upon experience with biologics production. We review current cell manufacturing integration, automation and provide an overview of some important considerations and best cGMP practices. Finally, we propose how multi-stage cell processing can be integrated into a single bioreactor, in order to develop streamlined cGMP-compliant cell processing systems.